Construction Workers’ Perceptions of Project Sacrifice and Safety Compliance - Hansen, Seng; Fassa, Ferdinand; Chandra, Vido (President University, 2025)
Many prior studies focused on construction workers' perceptions of safety compliance, but little or no research has been undertaken to investigate the relationship between construction project sacrifice and safety compliance. Construction project sacrifice – known as ‘tumbal proyek’ in the Indonesian Language is a socio-cultural phenomenon that still exists in Indonesian society. This research examines the perceptions of construction workers regarding project sacrifice and their relationship to workers’ compliance with construction safety management. A mixed-method approach was employed, which consisted of an integrative literature review and questionnaire surveys. In total, there were 102 valid survey responses, which were analysed using Structural Equation Modelling-Generalised Structured Component Analysis (SEM-GSCA). The analysis demonstrates a positive relationship between workers’ perceptions of project sacrifice and safety compliance. This study adds by offering empirical data on the phenomenon of project sacrifice and how workers' perceptions of it can influence the construction safety compliance in Indonesia. Although this is a context-specific study, the findings can serve as a reference for future research to enhance the safety climate in construction projects.